Determinants of Firm Value in Consumer Goods Industry Companies for the 2019–2025 Period - Dionysia Kowanda; Kartika Sukmawati; Endang Setyaningsih (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to analyze the effects of risk management disclosure, investment decisions, dividend policy, and profitability on firm value. The research objects consist of consumer goods industry companies listed on the Indonesia Stock Exchange during the 2019–2025 period. The research data were collected through documentation from financial statements, annual reports, and sustainability reports. The sampling technique employed purposive sampling with the following criteria: (1) the companies consistently published financial statements, annual reports, and sustainability reports throughout the research period; and (2) the companies did not experience losses or delisting, consistently distributed dividends, and did not undertake mergers or significant restructuring during the research period. Based on these criteria, 11 companies were selected as the research sample, resulting in 77 observations. Hypothesis testing was conducted using panel data regression analysis. Based on the Chow and Hausman test results, the Fixed Effect Model was selected as the most appropriate estimation model. The results indicate that investment decisions and profitability partially affect firm value, whereas risk management disclosure and dividend policy do not have a significant effect on the firm value of consumer goods industry companies during the 2019–2025 period. Simultaneously, risk management disclosure, investment decisions, dividend policy, and profitability affect firm value.